Positive electrode active material, method of manufacturing doped reconstituted nickel-rich positive electrode active material, and method of operating a battery

CN122930859APending Publication Date: 2026-10-16SAMSUNG SDI CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610437065.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-03
Filing Date
2026-04-03
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

尖晶石相表现出优异的Li传输动力学且可被认为是对于钝化层状正电极颗粒所期望的,但是控制表面相转变反应的根本(潜在)机制仍不清楚

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930859A_ABST
    Figure CN122930859A_ABST
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material, a method of manufacturing a doped reconstructed nickel-rich positive electrode active material, and a method of operating a battery. A doped reconstructed positive electrode active material is provided that includes an amount of at least about 85 mole percent nickel based on 100 mole percent of total metals in the positive electrode active material other than lithium, a bulk region, and a reconstructed region. The bulk region has a bulk crystal structure having a bulk space group and a bulk interplanar spacing, and the reconstructed region has a surface crystal structure having a surface space group and a surface interplanar spacing. The bulk space group is different from the surface space group, and the bulk interplanar spacing is greater than the surface interplanar spacing. A method of manufacturing the doped reconstructed positive electrode active material and a method of operating a rechargeable lithium battery that includes the doped reconstructed positive electrode active material are provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] One or more embodiments of this disclosure relate to a doped, reconstructed nickel-rich positive electrode active material having a bulk region and a reconstructed region, and a method for preparing said doped, reconstructed nickel-rich positive electrode active material. One or more embodiments relate to a rechargeable lithium battery including said doped, reconstructed nickel-rich positive electrode active material and a method for operating said rechargeable lithium battery. Background Technology

[0002] Electric vehicles and electronic devices such as smartphones, laptops, and / or the like use rechargeable lithium-ion batteries with high energy density as their power source. In response to the recent rapid proliferation of electric vehicles and electronic devices using rechargeable lithium-ion batteries, research has been actively conducted to develop rechargeable lithium-ion batteries with enhanced performance characteristics, such as high capacity and high energy density.

[0003] Positive electrode active materials used to provide rechargeable lithium-ion batteries with enhanced performance characteristics include Ni-rich layered oxides with at least 80% nickel (Ni). However, introducing more than 80% Ni into large, high-capacity, high-voltage, and / or high-energy-density rechargeable lithium-ion batteries has been challenging due to the physicochemical properties of Ni, which result in weak bulk and surface stability of these materials, for example, when operating at relatively high voltages. For instance, oxidized Ni can be unstable upon delithiation to produce a delithiated layered Ni-rich lithium transition metal oxide (LiTMO2) phase, which undergoes an irreversible phase transition, leading to subsequent capacity decay. This phase transition is primarily related to oxygen loss under high charge, resulting in spontaneous Ni reduction, particularly at the particle surface. Therefore, particle passivation (e.g., coating) that can suppress or reduce oxygen loss has been considered an effective method to extend the cycle life of Ni-rich LiTMO2 positive electrodes.

[0004] In chemically homogeneous particles, phase separation can be engineered by doping with foreign (heterogeneous) elements or by appropriately altering the transition metal composition. For example, doping heavy metal elements (e.g., Zr and W) into Ni-rich LiTMO2 particles results in the formation of an electrochemically inert rock-salt-like phase on the particle surface, while a layered phase is maintained in the particle bulk. The surface rock-salt phase has a Zr-rich (or W) composition and forms with a self-limiting thickness during electrochemical cycling. However, the details of how the rock-salt phase, which lacks a rapid Li diffusion pathway, provides a mechanism for reversible Li interphase insertion across the surface and interphase (interface) over extended cycles remain unclear.

[0005] Oxygen evolution (OE) can induce different types (or species) of surface phase transitions. For example, in a disordered rock salt positive electrode with a 20 mol% Li excess and certain transition metal compositions (e.g., Nb and Mn), a spinel-like surface phase, rather than rock salt, can form during the first few charge and discharge cycles, thus promoting long-term capacity stability. The spinel phase exhibits excellent Li transport kinetics and is considered desirable for passivating layered positive electrode particles; however, the fundamental (potential) mechanism controlling the surface phase transition reaction remains unclear. Without being limited by theory, designing spontaneous phase separation could provide functional particle structures to extend the cycle life of Ni-rich LiTMO2 positive electrodes, but how to obtain such structures is still unknown.

[0006] Therefore, it is desirable to improve the stability of the positive electrode active material for high-capacity or high-energy-density rechargeable lithium batteries, especially for high-voltage operating conditions.

[0007] The information disclosed in this background section is only used to enhance the understanding of the background of this disclosure, and therefore the information discussed in this background section does not necessarily constitute prior art. Summary of the Invention

[0008] One or more embodiments of this disclosure provide results from studies on altering particle structure and remodeling energies to produce more durable Ni-rich positive electrode active materials. The effects of stoichiometry and particle size distribution of the precursor mixture on the physicochemical properties of the Ni-rich positive electrode active material during synthesis and electrochemical cycling are presented herein. In one or more embodiments, the precursor and doping ratios are related to the thermodynamic and kinetic coordinates of the phase transition reaction, and the selection of these parameters can influence crystallite size, compositional gradient, and surface morphology to provide Ni-rich positive electrode active materials with highly reversible Li cycling performance.

[0009] One or more embodiments of this disclosure provide a method for forming a surface phase that is electrochemically stable and kinetically suitable for Ni-rich positive electrode active materials in a single firing step by selecting composition and particle size distribution. In one or more embodiments, the method provides a one-step (e.g., single-pot) method for manufacturing Ni-rich positive electrode active materials. The methods described herein do not require separate or additional process steps for applying a coating layer and form a conformal and cohesive surface phase for Ni-rich positive electrode active materials.

[0010] One or more aspects of embodiments of this disclosure relate to a positive electrode active material comprising at least about 85 mol% nickel, based on 100 mol% of total metals other than lithium in the positive electrode active material. The positive electrode active material includes a bulk region and a reconstructed region, and may be referred to as a doped, reconstructed, nickel-rich positive electrode active material. The bulk region has a bulk crystal structure having a bulk space group and a bulk interplanar spacing. The reconstructed region has a surface crystal structure including a surface space group and a surface interplanar spacing. The outer surface of the reconstructed region may be the outer surface of the doped, reconstructed, nickel-rich positive electrode active material. The bulk space group is different from the surface space group, and the bulk interplanar spacing is greater than the surface interplanar spacing.

[0011] In one or more embodiments, the bulk crystal structure may have a layered structure, and the bulk interplanar spacing may be from about 0.45 nanometers (nm) to about 0.50 nm.

[0012] In one or more embodiments, the body space group may be a rhombohedral (rhombohedral) space group having a (003) face and a (101) face adjacent to the (003) face.

[0013] In one or more embodiments, the surface interplanar spacing may be from about 0.20 nm to about 0.30 nm.

[0014] In one or more embodiments, the surface space group may be a face-centered cubic space group having (111) faces.

[0015] In one or more embodiments, the bulk interplanar spacing may be about 1.8 to about 2.2 times the surface interplanar spacing.

[0016] In one or more embodiments, the bulk crystal structure may have a [1,0,0] projection. In one or more embodiments, the bulk crystal structure may have layered symmetry.

[0017] In one or more embodiments, the surface crystal structure may have a [1,2,-1] projection. In one or more embodiments, the surface crystal structure may have cubic symmetry.

[0018] In one or more embodiments, the positive electrode active material may include elements selected from Group 4 (Group 4B), Group 6 (Group 6B), Group 13 and at least one element selected from Groups 8 to 10 of the periodic table.

[0019] In one or more embodiments, the positive electrode active material may include a bulk component (composition) represented by Chemical Formula 1 and a dopant component (composition) represented by Chemical Formula 2:

[0020] Chemical Formula 1

[0021] Li a1Ni n1 (M A y ) z O 2-b X b

[0022] Among them, each M A The elements M can be independently selected from Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sn, Sr, Ti, V, W, and Zr; each X can be independently selected from F, P, and S; 0.9 ≤ a1 ≤ 1.2; 0.8 ≤ n1 ≤ 0.995; each y can be an independent real number from 0 to 0.2; z can be an integer from 1 to 5, and 0 ≤ b ≤ 0.1. Here, the product of y and z (i.e., y*z) represents the dopant element M. A The total stoichiometry, and within the range of 0 to 0.2.

[0023] Chemical formula 2

[0024] Li a2 Ni n2 M B y2B M C y2C O2

[0025] Among them, M B It can be a transition metal selected from Group 4 (Group 4B) elements; M C It can be a transition metal selected from group 6 (group 6B); 0.9≤a2≤1.5; n2 and y2B can each be a real number from 0.27 to 0.39 independently; and the sum of n2+y2B+y2C can be equal to 2-a2.

[0026] In one or more embodiments, the bulk component may be represented by chemical formula 1A and the dopant component may be represented by chemical formula 2A:

[0027] Chemical Formula 1A

[0028] LiNi n Co y3 Al y4 O2

[0029] Where 0.9 ≤ n ≤ 0.995; 0.005 ≤ y3 ≤ 0.1; and the sum of n + y3 + y4 can be equal to 1.

[0030] Chemical formula 2A

[0031] Li 1.2 Ni 0.33 Ti 0.33 M C y5 O2

[0032] Among them, M C is Mo or W; and 0.10≤y5≤0.16.

[0033] In one or more embodiments, the reconstructed region is located on the surface of the positive electrode active material and includes group 4 and group 6 elements.

[0034] In one or more embodiments, the reconstructed region further includes 13 family elements and at least one element selected from families 8 to 10.

[0035] In one or more embodiments, the thickness of the reconstructed region is about 2% to about 20% of the size of the primary particles of the positive electrode active material.

[0036] In one or more embodiments, the positive electrode active material may include secondary particles, each secondary particle comprising an aggregation of primary particles. The secondary particles may have an average particle size (D50) of about 10 micrometers (μm) to about 18 μm. The primary particles may have an average particle size (D50) of about 15 nanometers (nm) to about 300 nm.

[0037] One or more aspects of embodiments of this disclosure relate to a method for manufacturing a doped, reconstructed nickel-rich positive electrode active material. The method includes providing a bulk component, providing a doped component (e.g., a doped reconstructed component), mixing the bulk component and the doped component to provide an intermediate, and heat-treating the intermediate in an oxidizing atmosphere. In one or more embodiments, the method includes a single heat treatment step (e.g., an action or task). In one or more embodiments, the method may be a one-step (e.g., single-pot) method for manufacturing a doped, reconstructed nickel-rich positive electrode active material.

[0038] In one or more embodiments, providing an intermediate includes mixing a bulk component and a dopant component in a weight ratio that may be from about 1:0.5 to about 1:0.001.

[0039] In one or more embodiments, providing the bulk components may include: mixing an amount (a certain amount) of a first Li compound, an amount of an Al salt, and a first solvent to form a first precursor; providing an additive portion of the first Li compound and an amount of a Ni composite oxide to the first precursor to form a first composite, wherein the Ni composite oxide is represented by chemical formula 3:

[0040] Chemical formula 3

[0041] LiNi n3 M D y6 O2

[0042] Among them, M DIt can be Co or Fe; 0.9≤n3≤0.995; and the sum of n3+y6 can be equal to 1; and the first complex is heat-treated.

[0043] In one or more embodiments, providing the doping components may include: mixing an amount of a second Li compound, an amount of Ni oxide, an amount of group 4 (group 4B) oxide, an amount of group 6 (group 6B) oxide, and a second solvent to form a second precursor; processing (treating) the second precursor; and heat-treating the second precursor.

[0044] In one or more embodiments of the method, the group 4 oxide may be TiO2, and the group 6 oxide may be MoO2 or WO3.

[0045] One or more aspects of embodiments of this disclosure relate to methods of operating a battery. For example, the battery may include: a positive electrode comprising a doped, reconstructed nickel-rich positive electrode active material as described herein; a negative electrode; and an electrolyte between the positive and negative electrodes. In one or more embodiments, if the operating voltage is at least about 3.9 volts (V) (e.g., when the operating voltage is at least about 3.9 volts (V)), the battery capacity retention may be at least about 85%.

[0046] Additional aspects of the implementation will be set forth in part in the description which follows, and will be apparent in part from the description, or may be learned by practice of the implementations of this disclosure presented.

[0047] The positive electrode active material according to one or more embodiments can be a doped, reconstructed nickel-rich positive electrode active material with high charge capacity and energy density. The doped, reconstructed nickel-rich positive electrode active material can have improved stability when included in a rechargeable lithium battery operating under high voltage conditions. Attached Figure Description

[0048] The foregoing and other objects and features of this disclosure will become more apparent to those skilled in the art from the exemplary embodiments described in more detail with reference to the accompanying drawings. In the drawings:

[0049] Figure 1 This illustrates a doped and reconstructed nickel-rich positive electrode active material according to one or more embodiments.

[0050] Figure 2A The X-ray powder diffraction (XRD) patterns of nickel-rich positive electrode active material and doped reconstructed nickel-rich positive electrode active material according to one or more embodiments are shown.

[0051] Figures 2B to 2D show Figure 2A The peak splitting portion (segment) of the XRD pattern.

[0052] Figure 3A This displays scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS) images of nickel-rich positive electrode active materials according to one or more embodiments.

[0053] Figure 3B and 3C Showing SEM and EDS images of the doped and reconstructed nickel-rich positive electrode active material according to one or more embodiments.

[0054] Figure 4A Showing cross-sectional SEM images of particles of nickel-rich positive electrode active material according to one or more embodiments.

[0055] Figure 4B show Figure 4A EDS intensity of nickel-rich positive electrode active material.

[0056] Figure 5A and 6A Showing cross-sectional SEM images of particles of doped and reconstructed nickel-rich positive electrode active material according to one or more embodiments.

[0057] Figure 5B and 6B show Figure 5A and 6A EDS intensity of the reconstructed nickel-rich positive electrode active material with doping.

[0058] Figure 7A and 8A Showing cross-sectional SEM images of the surface of particles of doped and reconstructed nickel-rich positive electrode active material according to one or more embodiments.

[0059] Figure 7B and 8B show Figure 7A and 8A EDS intensity of the reconstructed nickel-rich positive electrode active material particles.

[0060] Figures 9A to 9F These are high-resolution transmission electron microscopy (TEM) images of a doped and reconstructed nickel-rich positive electrode active material according to one or more embodiments.

[0061] Figures 10A to 10F It is a high-resolution TEM image of a reconstructed nickel-rich positive electrode active material according to one or more embodiments.

[0062] Figures 11A to 11DThis demonstrates the electrochemical performance of a coin cell comprising a nickel-rich positive electrode active material and a doped, reconstructed nickel-rich positive electrode active material according to one or more embodiments.

[0063] Figure 12 A cross-sectional perspective view is shown schematically according to one or more embodiments of a rechargeable lithium battery.

[0064] Figure 13 A cross-sectional view of a rechargeable lithium battery according to one or more embodiments is shown schematically.

[0065] Figure 14 and 15 A perspective view schematically showing a rechargeable lithium battery according to one or more embodiments. Detailed Implementation

[0066] To fully understand the configurations and effects of embodiments of this disclosure, exemplary embodiments of this disclosure will be described in more detail with reference to the accompanying drawings. However, it should be noted that these are provided as examples and this disclosure is not intended to be limited thereto and is defined solely by the scope of the appended claims and their equivalents, which are described in more detail herein. Rather, exemplary embodiments are provided only to disclose the subject matter of this disclosure and to enable those skilled in the art to fully appreciate its scope.

[0067] In the accompanying drawings, for clarity, the thickness of layers, films, regions, and / or the like may be exaggerated, and the same reference numerals always denote the same elements, and their repetition in the specification is not required. Unless otherwise stated in the specification, if a portion of a layer, film, region, and / or the like is referred to as "on" another portion, this includes not only the case where said portion is "directly" on the other portion, but also the case where another portion is inserted therein.

[0068] Unless otherwise stated in the specification, singular expressions may include plural expressions. Furthermore, unless otherwise stated, "A or B" may mean "including A, including B, or including both A and B".

[0069] In the specification, "combination thereof" may refer to mixtures, complexes, compositions, copolymers, alloys, blends and / or reaction products of the constituent elements.

[0070] As used herein, the terms “comprising,” “including,” and “having” are intended to indicate the presence of aspects, quantities, actions, tasks, elements, and / or combinations thereof (e.g., any suitable combinations thereof). However, the use of these terms does not prevent or exclude the possibility of the presence or addition of one or more other components, features, aspects, quantities, actions, tasks, elements, and / or combinations thereof (e.g., any suitable combinations thereof).

[0071] In one or more embodiments, the term "layer" as used herein includes not only shapes formed or provided across the entire surface when viewed from a plan view, but also shapes formed or provided on a portion of the surface.

[0072] It will be understood that although the terms “first,” “second,” “third,” and / or similar may be used herein to describe one or more suitable elements, components, regions, layers, and / or portions, these elements, components, regions, layers, and / or portions should not be limited by these terms. These terms are used only to distinguish one element, component, region, layer, or portion from another. Therefore, without departing from the spirit and scope of this disclosure, a first element, component, region, layer, or portion described herein may be referred to as a second element, component, region, layer, or portion.

[0073] As used herein, the term “and / or” includes any and all combinations of one or more of the associated listed items. Expressions such as “at least one of…”, “one of…”, “selected from…”, and “selected from” modify the entire list of elements before (or after) the list of elements and do not modify any individual element of the list. For example, the expressions “at least one of a to c”, “at least one of a, b, or c”, and “at least one of a, b, and / or c” can indicate only a, only b, only c, both a and b (e.g., simultaneously), both a and c (e.g., simultaneously), both b and c (e.g., simultaneously), all of a, b, and c, or variations thereof.

[0074] Spatially relative terms such as “below,” “under,” “lower,” “above,” “upper,” and / or similar may be used herein to readily describe the relationship between one element or feature and another. It will be understood that, in addition to the orientations shown in the figures, spatially relative terms are also intended to cover different orientations of the device in use or operation. For example, if the device in the figure is flipped, an element described as “below” or “under” another element or feature will be oriented as “above” another element or feature. Thus, the example term “below” may cover both orientations above and below (e.g., simultaneously). The device may be oriented in other ways (rotated 90 degrees or in other orientations), and the spatially relative terms used herein may be interpreted accordingly.

[0075] Unless otherwise defined, all terms used herein (including chemical, technical, and scientific terms) shall have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure pertains. It will be further understood that terms, such as those defined in commonly used dictionaries, shall be interpreted as having the meaning consistent with their meaning in the context of the relevant art and in this disclosure, and shall not be interpreted in an idealized or overly formal sense.

[0076] Example embodiments may be described herein with reference to cross-sectional views of schematic diagrams representing idealized embodiments. Thus, variations in shape from those illustrated are expected as a result of, for example, manufacturing techniques and / or tolerances. Therefore, the embodiments described herein should not be construed as limited to the specific shapes of the regions shown herein, but rather include, for example, deviations in shape due to manufacturing processes. For example, regions illustrated or described as flat may typically have rough and / or non-linear characteristics. Furthermore, sharp corners in the illustrations may be rounded. Therefore, the regions shown in the figures are schematic in nature, and their shapes are not intended to illustrate the precise shapes of the regions nor to limit the scope of the appended claims.

[0077] The term “may” should be understood to refer to “one or more embodiments of this disclosure,” some of which include the described elements and some of which exclude the described elements and / or include alternative elements. Similarly, alternative language such as “or” refers to “one or more embodiments of this disclosure,” each including the corresponding listed items. The description of features or aspects in each embodiment should typically be considered applicable to other similar features or aspects in other embodiments.

[0078] Furthermore, in this specification, the phrase "plan view" refers to the target portion viewed from the top, and the phrase "in cross-section" refers to the cross-section formed by vertically cutting the target portion viewed from the side.

[0079] In the context of this application and unless otherwise defined, the term “use” may be considered synonymous with the term “utilize”.

[0080] As used herein, the term "particle size" refers to the average diameter of the particle if the particle is spherical, and the average length of its major axis if the particle is non-spherical. For example, the average particle size can be measured by any suitable method in the art, such as by a particle size analyzer and / or by transmission electron microscopy images and / or scanning electron microscopy images. Values ​​for the average particle size can be obtained by performing dynamic light scattering analysis, data analysis, counting the number of particles in each particle size range, and calculating the obtained data. Unless otherwise defined, the average particle size can refer to the diameter (D) of particles having a cumulative volume of 50% of the particle size distribution. 50 If measurements are performed using laser diffraction, for example, the particles to be measured are dispersed in a dispersion medium and then introduced into a laser diffraction particle size measurement device of the relevant technology (e.g., the MT 3000 available from Microtrac, Ltd.), and after irradiation with ultrasound at an output of 60 W at approximately 28 kHz, the average particle size (D) based on the particle size distribution in the measurement device can be calculated. 50 As used herein, unless otherwise defined (e.g., when not otherwise defined), the average particle size refers to the diameter of the particle having a cumulative volume of 50% of the particle size in a particle size distribution obtained by randomly measuring the size (diameter or major axis length) of approximately 20 particles in a scanning electron microscope image. 50 ).

[0081] The following description includes non-limiting examples of values ​​for the quantities that are part of this disclosure. Example values ​​are described as example ranges for the quantities, and it will be understood that any and all of the following example ranges may include any subranges that begin and / or end with any of their values. The example range of “about 60% to about 80%” may also include, for example, about 60.0% to about 75%, about 68% to about 80.0%, about 68% to about 72%, about 69.5% to about 70.5%, about 70.0%, and about 70%.

[0082] Doped and reconstructed nickel-rich positive electrode active material

[0083] The positive electrode active material according to one or more embodiments of this disclosure includes a bulk region and a reconstructed region, and may be referred to as a doped reconstructed nickel-rich positive electrode active material. Figure 1 On the right is shown one or more embodiments of a doped, reconstructed nickel-rich positive electrode active material, wherein the bulk region is dark shaded and the reconstructed region is light shaded. Figure 1This document provides an overview of methods for manufacturing doped, reconstructed nickel-rich positive electrode active materials, as described in more detail elsewhere herein. In one or more embodiments, the doped, reconstructed nickel-rich positive electrode active material may be a layered lithium transition metal oxide, and the reconstructed regions provide a protective layer that reduces or suppresses oxygen loss from the nickel-rich bulk regions of the positive electrode active material.

[0084] The positive electrode active material comprises at least about 85 mol% of nickel, based on 100 mol% of total metals other than lithium in the positive electrode active material. For example, based on 100 mol% of total metals other than lithium in the positive electrode active material, the amount of nickel in the positive electrode active material may be about 85 wt% to about 99.5 wt%, about 85 wt% to about 99 wt%, about 85 wt% to about 98 wt%, about 85 wt% to about 95 wt%, about 90 wt% to about 95 wt%, or about 92 wt% to about 95 wt%.

[0085] The bulk region has a bulk crystal structure, which has a bulk space group and bulk interplanar spacing.

[0086] In one or more embodiments, the body space group may be a rhombohedral space group having a (003) face and a (101) face adjacent to the (003) face. For example, the body space group may be an R-3m space group.

[0087] In one or more embodiments, the bulk crystal structure may have a [1,0,0] projection. In one or more embodiments, the bulk crystal structure may have layered symmetry.

[0088] In one or more embodiments, the bulk crystal structure may have a layered structure, and the bulk interplanar spacing may be from about 0.45 nanometers (nm) to about 0.50 nm. For example, the bulk interplanar spacing may be from about 0.455 nm to about 0.495 nm, from about 0.46 nm to about 0.49 nm, or may be about 0.455 nm, 0.46 nm, 0.465 nm, 0.47 nm, 0.475 nm, 0.48 nm, 0.485 nm, 0.49 nm, or 0.495 nm.

[0089] The reconstructed region has a surface crystal structure with a surface space group and surface interplanar spacing. In one or more embodiments, the reconstructed region may be on or near the outer surface of the positive electrode active material. The bulk space group may differ from the surface space group, and the bulk interplanar spacing may be greater than the surface interplanar spacing. The term "reconstructed region" refers to a surface region of a nickel-rich positive electrode active material having a crystal structure with a lattice structure different from that of the bulk region. For example, the reconstructed region may be characterized by lattice fringes exhibiting a different interplanar spacing than the bulk region when observed by high-resolution transmission electron microscopy (HR-TEM), and may further exhibit a diffraction pattern indicating cubic symmetry, which can distinguish it from the layered structure of the bulk region, as analyzed by selected area electron diffraction (SAED). Furthermore, the reconstructed region may be formed by interdiffusion reactions between the dopant / coating components and the bulk components during mixing and calcination processes, resulting in a structural phase transition at the surface of the positive electrode active material.

[0090] In one or more embodiments, the surface space group may be a face-centered cubic space group with (111) faces. For example, the surface space group may be an Fm-3m space group.

[0091] In one or more embodiments, the surface crystal structure may have a [1,2,-1] projection. In one or more embodiments, the surface crystal structure may have cubic symmetry.

[0092] In one or more embodiments, the interplanar spacing may be from about 0.20 nm to about 0.30 nm. For example, the interplanar spacing may be from about 0.21 nm to about 0.29 nm, from about 0.23 nm to about 0.27 nm, or may be about 0.22 nm, 0.225 nm, 0.23 nm, 0.235 nm, 0.24 nm, 0.245 nm, 0.25 nm, 0.255 nm, or 0.265 nm.

[0093] In one or more embodiments, the bulk interplanar spacing may be about 1.8 to about 2.2 times the surface interplanar spacing. For example, the bulk interplanar spacing may be about 1.85 to about 2.15, about 1.95 to about 2.1 times the surface interplanar spacing, or may be about 1.85, 1.9, 1.95, 2, 2.05, 2.1, 2.15 or 2.2 times the surface interplanar spacing.

[0094] In one or more embodiments, the positive electrode active material as a whole may have an overall crystal structure having a rhombohedral structure, as determined by X-ray powder diffraction (XRD). For example, the overall crystal structure may have an R-3m space group and an α-NaFeO2 hexagonal structure. In one or more embodiments, the overall crystal structure may have a (003) / (104) peak intensity ratio of about 1.12 to about 1.30. For example, the (003) / (104) peak intensity ratio may be about 1.12 to about 1.30, about 1.14 to about 1.28, about 1.16 to about 1.26, or may be about 1.12, 1.13, 1.14, 1.15, 1.16, 1.17, 1.18, 1.19, 1.20, 1.21, 1.22, 1.23, 1.24, 1.25, 1.26, 1.27, 1.28, 1.29, or 1.30. In one or more embodiments, the overall crystal structure may have (108) / (110) plane peak splitting and (006) / (012) plane peak splitting.

[0095] In one or more embodiments, the bulk space group, bulk interplanar spacing, surface space group, and surface interplanar spacing can be determined by transmission electron microscopy (TEM).

[0096] In one or more embodiments, the projections of the bulk crystal structure and the surface crystal structure can be determined by selected area electron diffraction high-resolution transmission electron microscopy (SAED-TEM).

[0097] In one or more embodiments, the positive electrode active material may include at least three different elements selected from different groups of the periodic table. For example, the positive electrode active material may include elements selected from Group 4 (Group 4B), Group 6 (Group 6B), Group 13, and at least one element selected from Groups 8 to 10 of the periodic table. In one or more embodiments, the positive electrode active material may further include lithium.

[0098] In one or more embodiments, the positive electrode active material may include a bulk component represented by Chemical Formula 1 and a dopant component represented by Chemical Formula 2:

[0099] Chemical Formula 1

[0100] Li a1 Ni n1 (M A y ) z O 2-b X b

[0101] Among them, each M AEach x can be independently selected from Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sn, Sr, Ti, V, W, and Zr; each x can be independently selected from F, P, and S; 0.9 ≤ a1 ≤ 1.2; 0.8 ≤ n1 ≤ 0.995; each y can be an independent real number from 0 to 0.2; z can be an integer from 1 to 5, and 0 ≤ b ≤ 0.1.

[0102] In one or more embodiments, the bulk component may be LiNi 0.97 Co 0.02 Al 0.01 O2 (e.g., NCA97) is indicated.

[0103] Chemical formula 2

[0104] Li a2 Ni n2 M B y2B M C y2C O2

[0105] Among them, M B It can be a transition metal selected from group 4 elements; M C It can be a transition metal selected from group 6 elements; 0.9≤a2≤1.5; n2 and y2B can each be a real number from 0.27 to 0.39 independently; and the sum of n2+y2B+y2C can be equal to 2-a2.

[0106] In one or more embodiments, the bulk component may be represented by chemical formula 1A and the dopant component may be represented by chemical formula 2A:

[0107] Chemical Formula 1A

[0108] LiNi n Co y3 Al y4 O2

[0109] Where 0.9 ≤ n ≤ 0.995; 0.005 ≤ y3 ≤ 0.1; and the sum of n + y3 + y4 can be equal to 1.

[0110] Chemical formula 2A

[0111] Li 1.2 Ni 0.33 Ti 0.33 M C y5 O2

[0112] Among them, M C is Mo or W; and 0.10≤y5≤0.16.

[0113] In one or more embodiments, the dopant may be derived from Li 1.2 Ni 0.33 Ti 0.33 Mo 0.14 O2 (e.g., LNTM) or Li 1.2 Ni 0.33 Ti 0.33 W 0.14 O2 (e.g., LNTW) is indicated.

[0114] In one or more embodiments, the reconstructed region may be located on the surface of the positive electrode active material and may include group 4 and group 6 elements.

[0115] In one or more embodiments, the reconstructed region may further include 13 family elements and at least one element selected from families 8 to 10.

[0116] In one or more embodiments, the thickness of the reconstructed region may be from about 2% to about 20% of the size of the primary particles of the positive electrode active material. For example, the thickness of the reconstructed region may be from about 3% to about 18%, from about 5% to about 15%, or from about 8% to about 12% of the size of the primary particles of the positive electrode active material.

[0117] In one or more embodiments, the positive electrode active material may include secondary particles, each secondary particle comprising an aggregation of primary particles. The secondary particles may have an average particle size (D50) of about 10 micrometers (μm) to about 18 μm. For example, the secondary particles may have an average particle size (D50) of about 9 μm to about 16 μm, about 7 μm to about 15 μm, or about 4 μm to about 14 μm. The primary particles may have an average particle size (D50) of about 15 nanometers (nm) to about 300 nm. For example, the primary particles may have an average particle size (D50) of about 30 nm to about 500 nm, about 50 nm to about 400 nm, or about 80 nm to about 300 nm.

[0118] In one or more embodiments, the shapes of the secondary particles and the primary particles may each be independently selected from the following: irregular, spherical, hemispherical, and ellipsoidal.

[0119] The volume expansion rate of the positive electrode active material according to one or more embodiments may be at most about 1% to about 15%. Herein, "volume expansion rate" is the volume of the discharged positive electrode active material divided by the volume of the charged positive electrode active material; "discharged" means a state of at least 85%, at least 90%, at least 95%, or 100% discharge, and "charged" means a state of at least 85%, at least 90%, at least 95%, or 100% charge. For example, the volume expansion rate of the positive electrode active material may be about 1% to about 15%, about 2% to about 10%, or about 3% to about 8%. In one or more embodiments, the volume expansion rate of the positive electrode active material may be at most about 1% to about 15% (e.g., about 2% to about 10% or about 3% to about 8%).

[0120] The doped, reconstructed nickel-rich positive electrode active material of this disclosure may be a layered lithium transition metal oxide having a high charge capacity of greater than about 180 mAh / g in a charged state of at least about 3.9 volts (V) and is a suitable positive electrode active material for high energy density batteries. In one or more embodiments, the reconstructed region of the doped, reconstructed nickel-rich positive electrode active material extends the cycle life of Li-ion batteries (e.g., batteries operating at high states of charge).

[0121] In one or more embodiments, the reconfiguration region prevents or suppresses the release (e.g., loss) of lattice oxygen from the bulk region of the positive electrode active material (e.g., during the charging / discharging and / or delithiation / lithiation process of a rechargeable lithium battery).

[0122] In one or more embodiments, the reconstructed region may surround and protect the bulk region of the positive electrode active material from structural degradation and / or deterioration that mainly occurs at the surface of the positive electrode active material.

[0123] Using the positive electrode active material with reconfigurable regions of this disclosure in high-voltage batteries can improve stability and cycle life characteristics, while maximizing or increasing charge capacity and energy density.

[0124] Method for manufacturing doped and reconstructed nickel-rich positive electrode active materials

[0125] One or more aspects of embodiments of this disclosure relate to a method of manufacturing a doped, reconstructed nickel-rich positive electrode active material. The method includes the action or task of providing a bulk component, which may include mixing an amount of a first Li compound, an amount of an Al salt, and a first solvent to form a first precursor. For example, mixing may include using a blade mixer and at a temperature of about 60°C to about 110°C. The term "amount" in relation to the manufacturing method described herein may be or include "stoichiometric amount" or "excess amount." For example, an excess amount may be at most about 0.5 mol% excess, about 1 mol% excess, about 2 mol% excess, about 3 mol% excess, about 4 mol% excess, about 5 mol% excess, about 6 mol% excess, about 7 mol% excess, about 8 mol% excess, about 9 mol% excess, or about 10 mol% excess, and may include any subrange starting and / or ending with any of its values. As an example, for illustrative purposes only and not for limiting the scope of this disclosure, the amount of the first Li compound may be about 6 mol% in excess, and the amount of the Al salt may be about 5 mol% in excess.

[0126] In one or more embodiments, the first Li compound may be LiOH and / or Li₂CO₃. In one or more embodiments, the first Li compound may be LiOH.

[0127] In one or more embodiments, the Al salt may be an Al salt hydrate.

[0128] In one or more embodiments, the first solvent may be water or a non-aqueous organic solvent. In one or more embodiments, the first solvent may be water.

[0129] The method includes the action or task of providing a first Li compound with an added portion and a Ni composite oxide to a first precursor to form a first composite. For example, the nickel composite oxide may be provided at a temperature of about 100°C to about 160°C for a period of about 0.25 hours to about 24 hours.

[0130] In one or more embodiments, the nickel composite oxide may be represented by chemical formula 3:

[0131] Chemical formula 3

[0132] LiNi n3 M D y6 O2

[0133] Among them, M D It can be Co or Fe; 0.9 ≤ n3 ≤ 0.995; and the sum of n3 + y6 can be equal to 1. In one or more embodiments, the nickel composite oxide can be LiNi. 0.98 Co 0.02 O2.

[0134] The method includes heat-treating a first composite in an oxidizing atmosphere (e.g., a flowing oxygen atmosphere) to provide action or function of the bulk component. For example, the heat treatment may include a temperature of about 300°C to about 2000°C and a duration of about 0.25 hours to about 72 hours.

[0135] The method includes the action or task of providing a doped component (e.g., a doped remodeling component), which may include mixing an amount of a second Li compound, an amount of Ni oxide, an amount of a group 4 (group 4B) oxide, an amount of a group 6 (group 6B) oxide, and a second solvent to form a second precursor. For example, mixing may include using a blade mixer and at a temperature of about 60°C to about 110°C.

[0136] In one or more embodiments, the second Li compound may be LiOH and / or Li₂CO₃. In one or more embodiments, the second Li compound may be Li₂CO₃.

[0137] In one or more embodiments, the group 4 oxide may be TiO2 and the group 6 oxide may be MoO2 or WO3.

[0138] In one or more embodiments, the second solvent may be water or a non-aqueous organic solvent. In one or more embodiments, the second solvent may be acetone.

[0139] The method includes processing a second precursor and heat-treating the second precursor (e.g., in a flowing oxygen atmosphere) to provide the dopant component. Processing the second precursor may include ball milling in the presence of zirconia grinding media for a period of about 0.25 hours to about 72 hours. For example, heat treatment may include a temperature of about 300°C to about 2000°C for a period of about 0.25 hours to about 72 hours.

[0140] The method includes the action or task of mixing the bulk component and the dopant component to provide an intermediate. The method also includes the action or task of heat-treating the intermediate in an oxidizing atmosphere (e.g., a flowing oxygen atmosphere). For example, the heat treatment may include a temperature of about 300°C to about 2000°C and a duration of about 0.25 hours to about 72 hours.

[0141] In one or more embodiments, the method includes a single heat treatment step (e.g., action or task) of the intermediate. For example, the heat treatment intermediate may be performed as a single heat treatment.

[0142] In one or more embodiments, the action or task of providing the intermediate includes mixing the bulk component and the dopant component in a weight ratio that may be from about 1:0.5 to about 1:0.001. For example, the weight ratio may be from about 1:0.5 to about 1:0.005, from about 1:0.5 to about 1:0.01, or from about 1:0.5 to about 1:0.02.

[0143] In one or more embodiments, the first precursor, the first complex, the second precursor, and / or the intermediate may independently undergo a milling process (e.g., by ball milling) and / or be evaporated (e.g., to drying).

[0144] In one or more embodiments, the method may be a one-step (e.g., single-pot) method for producing a doped, reconstructed nickel-rich positive electrode active material.

[0145] positive electrode

[0146] In one or more embodiments, the positive electrode includes a positive electrode current collector and a layer of positive electrode active material on the positive electrode current collector, wherein the positive electrode active material layer includes the aforementioned positive electrode active materials as described herein. The positive electrode active material layer may be disposed on at least one surface of the positive electrode current collector (e.g., on one surface or two opposite surfaces). In addition to the aforementioned positive electrode active materials as described herein, the positive electrode active material layer may further include other types of positive electrode active materials. In embodiments, the positive electrode active material layer may optionally further include a binder, a conductive material (e.g., an electrically conductive material), and / or a combination thereof (e.g., any suitable combination).

[0147] According to one or more embodiments, the loading level of the positive electrode active material layer can be approximately 10 mg / cm². 2 (approximately 40 mg / cm) 2 For example, approximately 10 mg / cm 2 Approximately 30 mg / cm 2 or about 10 mg / cm 2 Approximately 20 mg / cm 2 In an embodiment, the density of the positive electrode active material layer in the final compressed positive electrode can be from about 3.3 g / cm³ to about 3.7 g / cc, for example from about 3.3 g / cc to about 3.6 g / cc or from about 3.4 g / cc to about 3.58 g / cc. If the positive electrode active material according to one or more embodiments is applied, a positive electrode satisfying the loading level and density of the positive electrode active material layer within the described range is suitable for achieving high-capacity, high-energy-density rechargeable lithium batteries.

[0148] Positive electrode current collector

[0149] The positive electrode current collector can be formed in the form of a plate, foil, and / or the like, and includes (e.g., composed of): indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), and / or alloys thereof. The thickness of the positive electrode current collector can range, for example, from about 1 micrometer (μm) to about 100 μm, from about 1 μm to about 50 μm, from about 5 μm to about 25 μm, or from about 10 μm to about 20 μm.

[0150] adhesive

[0151] The binder improves the adhesion properties between the positive electrode active material particles and with the current collector. Examples of binders may include, but are not limited to, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers (ethylene oxide-containing polymers), polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resins, (meth)acrylate resins, polyester resins, and nylon.

[0152] conductive materials

[0153] Conductive materials are included to provide electrical conductivity, and any suitable electrically conductive material can be used as the conductive material unless it causes undesirable chemical changes in the rechargeable lithium battery. Examples of conductive materials may include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers, carbon nanotubes and / or the like; metal-based materials including metal powders and / or metal fibers of copper, nickel, aluminum, silver and / or the like; electrically conductive polymers such as polyphenylene derivatives; and / or mixtures thereof (e.g., any suitable mixtures).

[0154] Based on a 100% by weight positive electrode active material layer, the respective contents (e.g., amounts) of the binder and conductive material may be from about 0.5% by weight to about 5% by weight.

[0155] Rechargeable lithium batteries

[0156] Some embodiments of this disclosure provide a battery that includes a positive electrode, a negative electrode, and an electrolyte between the positive and negative electrodes as described herein. As an example, the battery may be a rechargeable lithium-ion battery, which may include a positive electrode (positive), a negative electrode (negative), a separator between the positive and negative electrodes (negative), and an electrolyte. The electrolyte of a rechargeable lithium-ion battery may include an electrolyte solution as described elsewhere herein. In some embodiments, the rechargeable lithium-ion battery may be a solid-state (e.g., all-solid-state) rechargeable lithium-ion battery. Batteries according to one or more embodiments of this disclosure may be used in vehicles, electric vehicles, mobile phones, suitable electrical devices, and / or the like, but this disclosure is not limited thereto.

[0157] Depending on the shape of the rechargeable lithium battery, rechargeable lithium batteries can be classified as cylindrical, prismatic, pouch-shaped, coin-shaped, and / or similar. Figures 12 to 15 To illustrate a schematic diagram of a rechargeable lithium battery according to one or more embodiments, wherein... Figure 12 It is a cylindrical battery. Figure 13 It is a prismatic battery, and Figures 14 to 15 Each is a pouch-shaped battery. (See reference) Figures 12 to 15 The rechargeable lithium battery 100 includes an electrode assembly 40 and a housing 50. The electrode assembly 40 has a separator 30 between a positive electrode (positive electrode) 10 and a negative electrode (negative electrode) 20. The electrode assembly 40 is housed within the housing 50. The positive electrode (positive electrode) 10, the negative electrode (negative electrode) 20, and the separator 30 may be impregnated with an electrolyte. The rechargeable lithium battery 100 may include a sealing member 60 that seals the housing 50, such as... Figure 12 As shown. In Figure 13 In this context, the rechargeable lithium battery 100 may include a positive electrode (positive pole) lead connector 11, a positive electrode terminal 12, a negative electrode (negative pole) lead connector 21, and a negative electrode terminal 22. For example... Figures 14 to 15 As shown, the rechargeable lithium battery 100 includes electrode terminals 70, which may be a positive electrode (positive pole) terminal 71 and a negative electrode (negative pole) terminal 72, which serve as electrical paths for leading current formed in the electrode assembly 40 to the outside.

[0158] A rechargeable lithium battery according to one or more embodiments may be rechargeable at a high voltage or suitable for driving at a high voltage. For example, the upper charge limit voltage of the rechargeable lithium battery may be at least about 3.9 volts (V), or about 3.9 V to about 5 V, about 4 V to about 4.8 V, about 4.1 V to about 4.8 V, about 4.2 V to about 4.8 V, about 4.3 V to about 4.8 V, about 4.4 V to about 4.8 V, or about 4.5 V to about 4.7 V and / or similar.

[0159] The battery may have a theoretical capacity of at least about 180 mAh / g, for example about 180 mAh / g to about 290 mAh / g, about 200 mAh / g to about 280 mAh / g, or about 220 mAh / g to about 270 mAh / g.

[0160] Using the positive electrode active material in high-voltage batteries can improve stability and cycle life characteristics, while maximizing or increasing charging capacity and energy density.

[0161] negative electrode

[0162] The negative electrode may include a current collector and a negative electrode active material layer on the current collector, and the negative electrode active material layer may include a negative electrode active material and may further include a binder, a conductive material and / or a combination thereof (e.g., any suitable).

[0163] Negative electrode active material

[0164] The negative electrode active material may include materials that can reversibly insert / deintercalate lithium ions, lithium metal, lithium metal alloys, materials capable of doping / dedoping lithium, and / or transition metal oxides.

[0165] Materials capable of reversibly inserting / deintercalating lithium ions may include, for example, crystalline carbon, amorphous carbon, and / or combinations thereof (e.g., any suitable) as carbon-based negative electrode active materials. Crystalline carbon may be irregular, or sheet-like, flaky, spherical, or fibrous (e.g., in fibrous form), and may be or include natural graphite and / or artificial graphite. Amorphous carbon may be soft carbon, hard carbon, mesophase pitch carbonization products, calcined coke, and / or the like.

[0166] Lithium metal alloys include alloys of lithium and metals selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn.

[0167] Materials capable of doping / dedoping lithium can be Si-based and / or Sn-based negative electrode active materials. Si-based negative electrode active materials may include silicon, silicon-carbon composites, and SiO₂. x(0<x≤2), a Si-Q alloy (where Q is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements (other than Si), Group 15 elements, Group 16 elements, transition metals, rare earth elements, and / or any suitable combinations thereof, for example Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and / or any suitable combinations thereof), and / or any suitable combinations thereof. The Sn-based negative electrode active material may be Sn, SnO₂, SnO x (0<x≤2), a Sn alloy, and / or any suitable combinations thereof.

[0168] The silicon-carbon composite may be a composite of silicon and amorphous carbon. The average particle diameter (D of the silicon-carbon composite particles 50 ) may be, for example, about 0.5 μm to about 20 μm. According to one or more embodiments, the silicon-carbon composite may be in the form of silicon particles and amorphous carbon coated on the surfaces of the silicon particles. For example, it may include secondary particles (core) in which silicon primary particles are aggregated, and an amorphous carbon coating layer (shell) on the surfaces of the secondary particles. Amorphous carbon may also be present between the silicon primary particles, for example, the silicon primary particles may be coated with amorphous carbon. The secondary particles may be present dispersed in an amorphous carbon matrix.

[0169] The silicon-carbon composite may further include crystalline carbon. For example, the silicon-carbon composite may include a core comprising crystalline carbon and silicon particles, and an amorphous carbon coating layer on the surface of the core. The crystalline carbon may be artificial graphite, natural graphite, and / or any suitable combinations thereof. The amorphous carbon may include soft carbon and / or hard carbon, a mesophase pitch carbonized product, and / or calcined coke.

[0170] If the silicon-carbon composite includes silicon and amorphous carbon, based on 100 wt% of the silicon-carbon composite, the content (e.g., amount) of silicon may be about 10 wt% to about 50 wt%, and the content (e.g., amount) of amorphous carbon may be about 50 wt% to about 90 wt%. In some embodiments, if the composite includes silicon, amorphous carbon and crystalline carbon, based on 100 wt% of the silicon-carbon composite, the content (e.g., amount) of silicon may be about 10 wt% to about 50 wt%, the content (e.g., amount) of crystalline carbon may be about 10 wt% to about 70 wt%, and the content (e.g., amount) of amorphous carbon may be about 20 wt% to about 40 wt%.

[0171] In an embodiment, the thickness of the amorphous carbon coating layer may be about 5 nanometers (nm) to about 100 nm. The average particle diameter D of the silicon particles (primary particles) 50 ) may be about 10 nm to about 1 μm or about 10 nm to about 200 nm. The silicon particles may exist as elemental silicon, in the form of a silicon alloy, and / or in an oxidized form. The oxidized form of silicon may be represented by SiO x (0<x≤2). At this time, the atomic content (e.g., amount) ratio of Si:O indicating the oxidation degree may be about 99:1 to about 33:67. As used herein, if no additional definition is provided (e.g., when no additional definition is provided), the average particle diameter D 50 ) refers to the diameter of particles at a cumulative volume of about 50 vol% in the particle size distribution.

[0172] The Si-based negative electrode active material and / or Sn-based negative electrode active material may be mixed with the carbon-based negative electrode active material. If the Si-based negative electrode active material and / or Sn-based negative electrode active material are mixed with the carbon-based negative electrode active material for use, the mixing ratio may be a weight ratio of about 1:99 to about 90:10.

[0173] Binder

[0174] The binder serves to favorably adhere the negative electrode active material particles to each other, and also to adhere the negative electrode active material to the current collector. The binder may be a non-aqueous binder, an aqueous binder, a dry binder, and / or a combination thereof (e.g., any suitable combination).

[0175] The non-aqueous binder may include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyimide, and / or a combination thereof (e.g., any suitable combination).

[0176] The aqueous binder may include styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, and / or a combination thereof (e.g., any suitable combination).

[0177] When an aqueous binder is used as the negative electrode binder, a cellulose-based compound capable of imparting or increasing viscosity may be further included. As the cellulose-based compound, one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, or alkali metal salts thereof may be mixed and used. The alkali metal may be Na, K, or Li.

[0178] Dry adhesives can be polymeric materials that can be converted into fibers, and can be, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide and / or combinations thereof (e.g., any suitable combination).

[0179] conductive materials

[0180] Conductive materials are included to provide electrode conductivity (e.g., electrical conductivity), and any suitable electrically conductive material can be used as the conductive material unless it causes undesirable chemical changes in the rechargeable lithium battery. Examples of conductive materials include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers, carbon nanotubes, and / or the like; metal-based materials including metal powders and / or metal fibers of copper, nickel, aluminum, silver, and / or the like; electrically conductive polymers such as polyphenylene derivatives; and / or mixtures thereof (e.g., any suitable mixtures).

[0181] Based on a 100% by weight negative electrode active material layer, the content (e.g., amount) of the negative electrode active material can be from about 95% by weight to about 99.5% by weight, and based on the 100% by weight negative electrode active material layer, the content (e.g., amount) of the binder can be from about 0.5% by weight to about 5% by weight. For example, the negative electrode active material layer may include about 90% by weight to about 99% by weight of the negative electrode active material, about 0.5% by weight to about 5% by weight of the binder, and about 0.5% by weight to about 5% by weight of the conductive material.

[0182] Negative electrode current collector

[0183] The negative electrode current collector may include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), and / or alloys thereof, and may be in the form of foil, sheet, and / or foam. The thickness of the negative electrode current collector may be, for example, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 7 μm to about 10 μm.

[0184] electrolytes

[0185] In one or more embodiments, the electrolyte may be an electrolyte solution or a solid electrolyte. For example, the electrolyte may be an electrolyte solution for use in rechargeable lithium batteries, and the electrolyte solution may include a non-aqueous organic solvent and a lithium salt. In some embodiments, the electrolyte may be a solid electrolyte for use in solid-state (e.g., all-solid-state) rechargeable lithium batteries.

[0186] Non-aqueous organic solvents are used as media for transporting ions that participate in the electrochemical reactions of the battery. Non-aqueous organic solvents may be carbonate (carbonate-based) solvents, ester (ester-based) solvents, ether (ether-based) solvents, ketone (ketone-based) solvents and / or alcohol (alcohol-based) solvents, aprotic solvents and / or combinations thereof (e.g., any suitable combination).

[0187] Carbonate solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butyl carbonate (BC), and / or the like. Ester solvents may include methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, decanolactone, mevalonolactone, valproic acid lactone, caprolactone, and / or the like. Ether solvents may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, and / or the like. In some embodiments, ketone solvents may include cyclohexanone and / or the like. Alcohol solvents may include ethanol, isopropanol and / or the like, and aprotic solvents may include nitriles such as R-CN (where R is a C2 to C20 straight-chain, branched or cyclic hydrocarbon group, and may include double bonds, aromatic rings or ether groups and / or the like); amides such as dimethylformamide; dioxolane such as 1,3-dioxolane, 1,4-dioxolane and / or the like; sulfolane and / or the like.

[0188] Non-aqueous organic solvents may be used alone or in mixtures of two or more types, and if two or more types are used in mixtures, the mixing ratio may be appropriately or suitably adjusted according to the desired or suitable battery performance.

[0189] If carbonate solvents are used, cyclic carbonates and chain carbonates can be mixed and used, and cyclic carbonates and chain carbonates can be mixed in a volume ratio of about 1:1 to about 1:9.

[0190] Non-aqueous organic solvents may further include aromatic hydrocarbon organic solvents. For example, carbonate solvents and aromatic hydrocarbon organic solvents may be mixed and used in a volume ratio of about 1:1 to about 30:1.

[0191] The electrolyte solution may further include vinylene carbonate, vinylene carbonate and / or ethylene carbonate compounds to improve battery cycle life.

[0192] Examples of ethylene carbonate compounds may include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.

[0193] Lithium salts dissolved in organic solvents supply lithium ions in the battery, enabling basic operation of rechargeable lithium batteries and improving lithium ion transport between the positive and negative electrodes. Examples of lithium salts may include at least one selected from the following: LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO2C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2 (where x and y are integers from 1 to 20), lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalate)phosphate (LiDFBOP), and lithium bis(oxalate)borate (LiBOB).

[0194] The concentration of the lithium salt can be in the range of about 0.1 M to about 2.0 M. If the concentration of the lithium salt is within this range, the electrolyte solution has appropriate or suitable ionic conductivity and viscosity, and therefore excellent or suitable performance can be achieved and lithium ions can move efficiently.

[0195] Solid electrolytes may include any material suitable for use as ion-conducting materials, with non-limiting examples including inorganic solid electrolytes, crystalline solid electrolytes, amorphous solid electrolytes, or combinations thereof. Solid electrolytes may be, for example, sulfide-based solid electrolytes, oxide-based solid electrolytes, or combinations thereof. Sulfide-based solid electrolytes may include, for example, Li, S, and P, and may optionally further include halogen elements. Sulfide-based solid electrolytes may be selected from those used in the electrolyte layer. For example, sulfide-based solid electrolytes may have a content of at least about 1 × 10⁻⁶ at room temperature. -5 Ionic conductivity in Siemens per centimeter (S / cm). Oxide-based solid electrolytes may include, for example, Li, O, and transition metals, and may optionally further include other elements. For example, an oxide-based solid electrolyte may have an ionic conductivity of at least about 1 × 10⁻⁶ at room temperature. -5 Solid electrolytes with an ionic conductivity of S / cm. Oxide-based solid electrolytes can be selected from those suitable for use in the electrolyte layer.

[0196] diaphragm

[0197] Depending on the type of rechargeable lithium battery, a separator may be present between the positive and negative electrodes. The separator may include multilayer films of polyethylene, polypropylene, polyvinylidene fluoride, or two or more layers thereof, and mixed multilayer films such as polyethylene / polypropylene two-layer separators, polyethylene / polypropylene / polyethylene three-layer separators, polypropylene / polyethylene / polypropylene three-layer separators, and / or similar materials.

[0198] The diaphragm may include a porous substrate and a coating on one or both surfaces (e.g., opposite surfaces) of the porous substrate, comprising organic materials, inorganic materials and / or combinations thereof (e.g., any suitable combination).

[0199] The porous substrate may be a polymer film formed from any of the following polymers: polyolefins such as polyethylene and polypropylene; polyesters such as polyethylene terephthalate and polybutylene terephthalate; polyacetal; polyamide; polyimide; polycarbonate; polyetherketone; polyaryletherketone; polyetherimide; polyamideimide; polybenzimidazole; polyethersulfone; polyphenylene ether; cyclic olefin copolymers; polyphenylene sulfide; polyethylene naphthalate; and polytetrafluoroethylene (PTFE; Teflon®); or copolymers or mixtures of two or more thereof. The porous substrate may include glass fiber, or may include a composite film of polymer and glass fiber.

[0200] The porous substrate may have a thickness of about 1 μm to about 40 μm, for example, about 1 μm to about 30 μm, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 10 μm to about 15 μm.

[0201] Organic materials may include (meth)acrylic acid copolymers, which include a first structural unit and a second structural unit derived from (meth)acrylamide, the second structural unit including at least one structural unit derived from (meth)acrylic acid or (meth)acrylate and a structural unit derived from (meth)acryloylaminosulfonic acid or a salt thereof.

[0202] Inorganic materials may include inorganic particles selected from Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, and / or (e.g., any suitable) combinations thereof, but this disclosure is not limited thereto. The average particle size (D) of the inorganic particles... 50 The wavelength can be from about 1 nm to about 2000 nm, for example from about 100 nm to about 1000 nm or from about 100 nm to about 700 nm.

[0203] Organic and inorganic materials can be mixed in a single coating, or coatings comprising organic materials and coatings comprising inorganic materials can be stacked.

[0204] The coating thickness can be from about 0.5 μm to about 20 μm, for example from about 1 μm to about 10 μm or from about 1 μm to about 5 μm.

[0205] Methods for operating rechargeable lithium batteries

[0206] One or more aspects of embodiments of this disclosure relate to methods of operating a battery. For example, the battery may include: a positive electrode comprising a doped, reconstructed nickel-rich positive electrode active material as described herein; a negative electrode; and an electrolyte between the positive and negative electrodes. In one or more embodiments, if the operating voltage is at least about 3.9 volts (V) (e.g., when the operating voltage is at least about 3.9 volts (V)), the battery's capacity retention may be at least about 85%. For example, the battery may be a rechargeable lithium-ion battery or a solid-state battery.

[0207] In one or more embodiments, the amount of oxygen released from the battery during operation may be at least about 50% less than the amount of oxygen released during operation of a comparable battery that includes a positive electrode active material that does not include the remodeling region described herein. For example, the amount of oxygen released may be about 50% to about 99%, about 50% to about 95%, about 50% to about 90%, about 50% to about 80%, about 50% to about 70%, about 50% to about 60%, about 60% to about 95%, about 60% to about 90%, about 60% to about 80%, about 60% to about 70%, about 70% to about 95%, about 70% to about 90%, about 70% to about 85%, about 70% to about 80%, about 80% to about 95%, about 80% to about 90%, about 85% to about 95%, or about 85% to about 90%. For example, amounts of oxygen as described herein may be released from the battery, its positive electrode active material, and / or its nickel complex oxide, and may be released during battery charging and / or battery discharging.

[0208] The method may include charging the battery to an upper limit voltage of at least about 3 V. For example, the upper limit voltage may be about 3 V to about 4.8 V, about 3 V to about 4.7 V, about 3 V to about 4.5 V, about 3 V to about 3.9 V, about 3.1 V to about 3.8 V, about 3.2 V to about 3.7 V, or about 3.3 V to about 3.6 V. The method may include operating the battery in a range of about 3 V to about 4.8 V, such as about 3 V to about 4.7 V, about 3 V to about 4.5 V, about 3.2 V to about 4.8 V, about 3.5 V to about 4.8 V, about 4 V to about 4.8 V, about 4.3 V to about 4.8 V, about 4.4 V to about 4.8 V, or about 4.5 V to about 4.7 V.

[0209] The method may include operating the battery at a rate of about 0.2 C to about 10 C, for example about 0.5 C to about 10 C, about 1 C to about 8 C, about 1 C to about 7 C, about 1 C to about 6 C, about 1 C to about 5 C, about 1 C to about 4 C, about 1 C to about 3 C, about 1 C to about 2 C, about 2 C to about 8 C, about 2 C to about 6 C, about 2 C to about 5 C, about 2 C to about 4 C, about 2 C to about 3 C, about 3 C to about 8 C, about 3 C to about 7 C, about 3 C to about 6 C, about 3 C to about 5 C, or about 3 C to about 4 C.

[0210] The method may include an action or task of operating the battery for at least about 50 charge-discharge cycles. For example, the total number of charge-discharge cycles operated on the battery may be about 50 to about 1000, about 50 to about 800, about 50 to about 700, about 50 to about 500, about 50 to about 400, about 50 to about 300, about 50 to about 200, about 50 to about 100, about 100 to about 500, about 100 to about 400, about 100 to about 300, about 150 to about 500, about 150 to about 400, about 150 to about 300, about 150 to about 200, about 200 to about 500, about 200 to about 400, about 200 to about 300, or about 100 to about 200.

[0211] Methods of operating a battery may include achieving or realizing a capacity retention of at least about 60%. As used herein, the term "capacity retention" refers to the percentage of the battery's discharged capacity after operation at the voltage range, C-rate range, and total number of charge-discharge cycles as described herein, relative to the battery's initial discharged capacity before operation. For example, operating a battery may achieve, reach, or realize a capacity retention of about 65% to about 99%, about 70% to about 95%, about 70% to about 90%, about 70% to about 85%, about 70% to about 80%, about 70% to about 75%, about 75% to about 95%, about 75% to about 90%, about 75% to about 85%, about 75% to about 80%, about 80% to about 95%, about 80% to about 85%, about 85% to about 95%, or about 85% to about 90%.

[0212] In the following description, a doped and reconstructed nickel-rich positive electrode active material according to one or more embodiments of the present disclosure will be further illustrated with reference to one or more examples. The examples are merely illustrative to aid in understanding the subject matter of the present disclosure, and the scope of the disclosure is not limited thereto.

[0213] Example

[0214] Preparation of bulk components of nickel-rich positive electrode active material

[0215] The bulk component of the nickel-rich positive electrode active material is LiNi 0.97 Co 0.02 Al 0.01 O2 (NCA97) is formed by mixing stoichiometric amounts of the precursor Ni as follows: 0.98 Co 0.02 O, LiOH, and Al(NO3)3·9H2O. Disperse Al(NO3)3·9H2O in deionized water and mix using a blade mixer at 80°C for 30 minutes. Add 6 mol% excess LiOH, for example, to compensate for possible Li loss during calcination. Add stoichiometric amounts of Ni at 130°C over a 2-hour period. 0.98 Co 0.02 O is slowly added to the solution. The solution is then air-dried overnight in an oven at 90°C. After drying, the mixture is manually ground to obtain the bulk component as a fine powder.

[0216] Preparation of doped reconstructed components

[0217] To synthesize Li 1.2 Ni 0.33 Ti 0.33 Mo 0.14 O2-doped reconstructed (DRX) composition (LNTM) was synthesized using precursors Li2CO3, NiO, TiO2, and MoO2.1.2 Ni 0.33 Ti 0.33 W 0.14 O2-doped reconstructed (DRX) composition (LNTW) was prepared using precursors Li2CO3, NiO, TiO2, and WO3. The precursors were dispersed in acetone in stoichiometric proportions and ball-milled in a polypropylene tank using zirconium oxide grinding media for 18 hours, followed by drying in an oven at 90°C overnight. After drying, the mixtures were manually ground to obtain the DRX composition as a fine powder.

[0218] Synthesis of doped and reconstructed nickel-rich positive electrode active materials

[0219] One of the bulk component NCA97 powder and the doped reconstructed (DRX) component powder is manually mixed at a weight ratio of 1:0.02 to provide an intermediate, which is then calcined in a tube furnace at 750°C for 15 hours in a flowing oxygen atmosphere to provide the doped reconstructed nickel-rich positive electrode active material LNTM-NCA97 or LNTW-NCA97.

[0220] Evaluation was conducted using X-ray powder diffraction, scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDS).

[0221] Figure 2A The X-ray powder diffraction (XRD) patterns of the nickel-rich positive electrode active material NCA97 prepared without DRX introduction and the doped reconstructed positive electrode active materials LNTM-NCA97 and LNTW-NCA97 are shown. All three samples have a well-defined (well-defined) rhombohedral structure, which can be indexed to the hexagonal structure of α-NaFeO2 corresponding to the R-3m space group. Note that several small, unsignified peaks are attributable to the diffractometer and are not sample-related. No additional impurity diffraction peaks were generated after DRX addition, indicating that DRX addition does not change the crystal structure of NCA97. Since no DRX peaks were observed, we consider the relative amount of DRX content to be too small to be observed by XRD. Figure 2B and 2C Peak splitting is shown for the (006) / (012) plane and the (108) / (110) plane, respectively. This was clearly observed for NCA97, LNTM-NCA97 and LNTW-NCA97, indicating that the structure of each product is basically layered. Figure 2D The results show that for the (003) / (104) plane, the peak intensity ratio is 1.14 for NCA97, 1.16 for LNTM-NCA97, and 1.21 for LNTW-NCA97, all of which indicate that the structure of each product is substantially layered to provide high Li activation.

[0222] The elemental distribution on the surface and across the cross-section of the NCA97, LNTM-NCA97 and LNTW-NCA97 prepared as described herein was evaluated using scanning electron microscopy with energy-dispersive X-ray spectroscopy (EDS) and focused ion beam etching. Figure 3A (Top left) SEM image of NCA97 shows spherical particles with an average diameter of approximately 14 micrometers (μm). These spherical particles are secondary particles formed by the aggregation of primary particles with an average diameter of approximately 300 nanometers (nm). EDS mapping (surface scan) results indicate that the surface of NCA97 possesses Al (top right, Figure 3A ), Ni (lower left, Figure 3A ) and Co (bottom right, Figure 3A The uniform distribution of ).

[0223] Figure 3B and 3C (Top left) SEM images of LNTM-NCA97 and LNTW-NCA97 are shown respectively, indicating that the spherical particles have the same properties as... Figure 3A The NCA97 spherical particles (top left) are essentially of the same size; for example, secondary particles with an average diameter of about 14 μm are an aggregation of primary particles with an average diameter of about 300 nm. EDS mapping results indicate that the addition of the DRX precursor mixture leads to a significant increase in the size of Al (top right, ...). Figures 3B to 3C ), Mo (lower left, Figure 3B ), W (lower left, Figure 3C ) and Ti (bottom right, Figures 3B to 3C The surface composition of LNTM-NCA97 and LNTW-NCA97 varies. LNTM-NCA97 and LNTW-NCA97 show uniform distributions of Ti-Mo and Ti-W, respectively.

[0224] Evaluation of cross-sectional SEM images and EDS intensity

[0225] Figure 4A Showing cross-sectional SEM images of NCA97 particles, and Figure 4B The image shows a set of normalized EDS intensities obtained from line scans of NCA97 particles, with error bars indicating results obtained in a series of five replicates. The line scan results indicate that Al concentration tends to be higher in the surface region of the secondary particles, with a concentrated (condensed) Al layer approximately 1 μm thick. In contrast, Co intensity is relatively uniform throughout the particles. Figure 5A Showing cross-sectional SEM images of LNTM-NCA97 particles, and Figure 5BThis displays a set of normalized EDS intensities obtained from line scans of LNTM-NCA97 particles, with error bars indicating the results obtained in a series of five repeated tests. Figure 6A Showing cross-sectional SEM images of LNTW-NCA97 particles and Figure 6B The table shows a set of normalized EDS intensities obtained from line scans of LNTW-NCA97 particles, with error bars indicating results obtained in a series of five repeated tests. The results indicate that the concentrations of DRX-specific elements (e.g., Ti and Mo for LNTM and Ti and W for LNTW) are relatively high in the surface region of the particles.

[0226] Figure 7A and 8A Cross-sectional SEM images of LNTM-NCA97 primary particles and LNTW-NCA97 primary particles near the surface of the secondary particles are shown, respectively. Figure 7B and 8B A set of normalized EDS intensities obtained from line scans across LNTM-NCA97 and LNTW-NCA97 primary particles are displayed. The results show that the distributions of Ni, Co, and Al across the primary particles are consistent (e.g., remain similar) for both types of particles. In contrast, Ti and Mo for LNTM-NCA97 and Ti and W for LNTW-NCA97 show fluctuations consistent with the locations of the EDS points. The results indicate that the concentrations of DRX-specific elements (e.g., Ti and Mo for LNTM and Ti and W for LNTW) are larger in the surface regions of the primary particles.

[0227] Evaluation using high-resolution transmission electron microscopy (TEM)

[0228] Figure 9A and 9B These are high-resolution transmission electron microscopy (TEM) images of the LNTM-NCA97 particles, confirming the crystal structure of the surface phase observed in the SEM images discussed herein. The particle surface exhibits unique lattice fringe with different interplanar spacings than the bulk, as indicated by the dashed lines. The bulk sites of the LNTM-NCA97 particles have a well-ordered structure with an interplanar spacing of 0.475 nm, consistent with the (003) plane adjacent to the (101) plane of the R-3m layered structure. In contrast, the surface sites have a different interplanar spacing of 0.24 nm, which can be correlated with the (111) plane of the Fm-3m space group from the DRX structure. Figure 9C , 9DImages 9E and 9F are selected area electron diffraction (SAED) images of LNTM-NCA97 particles, which were performed to further investigate the surface phase. Three distinct patterns were observed by moving the selected aperture (aperture) from region I to II and from region II to III. First, the corresponding SAED pattern in region I can be indexed as a [1,2,-1] projection from the Fm-3m structure, revealing that these particles are DRX with cubic symmetry. The SAED pattern in region II includes a [1,2,-3] projection from the DRX and a [1,0,0] projection from the R-3m structure. In region III, the pattern shows a strong [1,0,0] projection of a layered structure. This is clear and conclusive evidence that the DRX phase exists on the surface of the layered structure of the LNTM-NCA97 particles.

[0229] Figure 10A and 10B These are high-resolution transmission electron microscopy (TEM) images of LNTW-NCA97 particles, which confirm the crystal structure of the surface phase observed in the SEM images discussed in this paper. Figure 10C , 10D Images 10E and 10F are selected area electron diffraction (SAED) images of the LNTW-NCA97 particles, which were performed to further investigate the surface phase. The results show that the morphology of the LNTW-NCA97 particles is substantially the same as that of the LNTM-NCA97 particles discussed in the previous section. For example, a surface Fm-3m phase separate from the layered R-3m structure was observed.

[0230] Evaluation of battery cell performance

[0231] The performance of the electrochemical cell was evaluated as follows: CR2032 coin cell was prepared using lithium metal as the counter electrode and one of the NCA97 positive electrode, LNTM-NCA97 positive electrode, or LNTW-NCA97 positive electrode.

[0232] To prepare the positive electrode, 80 wt% of the active material, 15 wt% of carbon black (Super P, MTI), and 5 wt% of polytetrafluoroethylene (DuPont) were dry-mixed in an argon-filled glove box. The agglomerates (lumps) of the positive electrode mixture were then rolled (roll-pressed) into a 200 μm thick film and passed through a 6 mm diameter punch at approximately 8 mg / cm³. 2 The load density is cut.

[0233] The positive electrode, along with a glass fiber separator (Whatman, GF / F) and Li metal (Wellcos, S. Korea) as the negative electrode, was placed in a 2032-type coin cell and immersed in a commercial carbonate electrolyte (Sigma-Aldrich, 1 M LiPF6 dissolved in ethylene carbonate and dimethyl carbonate in a 50:50 volume ratio).

[0234] Figure 11A Charge-discharge curves for the second cycle of three different positive electrodes are shown at 0.2C current density (1C: 270 mA / g, voltage window: 3.0–4.3 V) and room temperature. NCA97, LNTM-NCA97, and LNTW-NCA97 exhibit similar discharge capacities of 221 mAh / g, 226 mAh / g, and 216 mAh / g, respectively.

[0235] Figure 11B The results show the differential capacity (dQ / dV) curve as a function of voltage and can be used to evaluate redox kinetics and phase transitions. The peaks indicate first-order phase transitions related to abrupt contraction / expansion of lattice parameters and / or Li / vacancy ordering during charging and discharging. Figure 11B The results show that the three positive electrodes each undergo similar phase transitions during delithiation, from an initial hexagonal phase (H1) to a monoclinic phase (M) and two additional hexagonal phases (H2 and H3). The H2-H3 phase transition is known to be the cause of capacity decay in Ni-rich positive electrode materials. It was observed that during charging, the H2-H3 redox peaks of the LNTM-NCA97 and LNTW-NCA97 positive electrodes exhibited smaller peak intensities and higher voltages compared to the NCA97 positive electrode, indicating that the unfavorable H2-H3 phase transition can be pushed to higher voltages. This observation is well consistent with the improved capacity retention, as the suppressed H2-H3 phase transition mitigates structural instability.

[0236] Figure 11C The results of the second charge-discharge curves at 1 C are shown between 3 V and 4.35 V, and the initial capacities of the NCA97 positive electrode, LNTM-NCA97 positive electrode, and LNTW-NCA97 positive electrode are 229 mAh / g, 241 mAh / g, and 231 mAh / g, respectively. Figure 11DThe data shows the capacity changes of the three positive electrodes with respect to the number of cycles after 50 cycles at 1C and 45°C. Using the NCA97 positive electrode resulted in the greatest capacity decay, for example, 78% capacity retention after 50 cycles. Using the LNTM-NCA97 positive electrode resulted in 79% capacity retention after 50 cycles due to rapid decay after 30 cycles, which could be attributed to faster electrolyte decomposition at 45°C due to its higher capacity compared to NCA97. Using the LNTW-NCA97 positive electrode resulted in suitable or excellent cycling performance with 89% capacity retention after 50 cycles.

[0237] According to one or more embodiments of this disclosure, the electrochemical properties of nickel-rich positive electrode active materials can be enhanced or improved when a doped reconstructed (DRX) precursor mixture is used to prepare the material. For example, the DRX precursor mixture can provide a doped reconstructed nickel-rich positive electrode active material with a passivated doped reconstructed surface. In one or more embodiments, the doped reconstructed surface can provide a protective layer that reduces or prevents degradation of the surface of the bulk nickel-rich positive electrode active material and / or the doped reconstructed nickel-rich positive electrode active material.

[0238] Terms such as “substantially,” “about,” and “approximately” are used as relative terms and not as terms of degree, and are intended to explain the inherent deviations in measured or calculated values ​​that would be recognized by a person skilled in the art. They may include the stated value and an acceptable range of deviation as determined by a person skilled in the art taking into account the limitations and errors associated with the measurement of that quantity. For example, “about” may refer to one or more standard deviations relative to the stated value, or ±30%, 20%, 10%, or 5%.

[0239] The numerical ranges disclosed herein include, and are intended to be disclosed, all subranges containing the same numerical precision. For example, the range “1.0 to 10.0” includes all subranges having a minimum value equal to or greater than 1.0 and a maximum value equal to or less than 10.0, such as 2.4 to 7.6. Therefore, the applicant reserves the right to amend this specification (including the claims) to expressly describe any subranges included within the ranges expressly described herein.

[0240] The battery management system (BMS) device and / or any other related device or component described herein according to embodiments of this disclosure can be implemented using any suitable hardware, firmware (e.g., application-specific integrated circuit), software, or a combination of software, firmware, and hardware. For example, components of the device may be formed on a single integrated circuit (IC) chip or on separate IC chips. Furthermore, components of the device may be implemented on a flexible printed circuit film, a tape-on-a-package (TCP), a printed circuit board (PCB), or formed on a substrate. Additionally, components of the device may be processes or threads running on one or more processors in one or more computing devices, executing computer program instructions and interacting with other system components to perform the functions described herein. The computer program instructions are stored in memory, which may be implemented in a computing device using standard storage devices (e.g., random access memory (RAM)). The computer program instructions may also be stored in other non-transitory computer-readable media such as CD-ROMs, flash drives, and / or the like. Furthermore, those skilled in the art will recognize that, without departing from the scope of this disclosure, the functionality of a computing device may be combined or integrated into a single computing device, or the functionality of a particular computing device may be distributed across one or more other computing devices.

[0241] Example embodiments of this disclosure have been described, but this disclosure is not limited thereto. One or more suitable other modifications may be made within the scope of, and are included within, the scope of, the claims, the detailed description of this disclosure, and the accompanying drawings. Therefore, any modified embodiments may be understood without separating them from the technical spirit and aspects of this disclosure, and the modified embodiments are within the scope of the appended claims and their equivalents.

[0242] Figure Labels

[0243] 100: Rechargeable lithium battery; 10: Positive electrode

[0244] 11: Positive electrode lead connector 12: Positive electrode terminal

[0245] 20: Negative electrode 21: Negative electrode lead connector

[0246] 22: Negative electrode terminal; 30: Diaphragm

[0247] 40: Electrode assembly; 50: Housing

[0248] 60: Sealing component; 70: Electrode terminal piece

[0249] 71: Positive electrode connector; 72: Negative electrode connector

Claims

1. Positive electrode active material, including: At least 85 mol% of nickel, based on 100 mol% of total metals other than lithium in the positive electrode active material; Body region; and Reconstruct the region; The bulk region has a bulk crystal structure, which has a bulk space group and bulk interplanar spacing. The reconstructed region has a surface crystal structure, which has a surface space group and surface interplanar spacing. The body space group is different from the surface space group. The bulk interplanar spacing is greater than the surface interplanar spacing, and The positive electrode active material is a doped, reconstructed nickel-rich positive electrode active material.

2. The positive electrode active material according to claim 1, wherein: The bulk crystal structure has a layered structure, and The bulk interplanar spacing is 0.45 nanometers (nm) to 0.50 nm.

3. The positive electrode active material according to claim 1, wherein the bulk space group is a rhombohedral space group having a (003) face and a (101) face adjacent to the (003) face.

4. The positive electrode active material according to claim 1, wherein the interplanar spacing is 0.20 nm to 0.30 nm.

5. The positive electrode active material according to claim 1, wherein the surface space group is a face-centered cubic space group having (111) faces.

6. The positive electrode active material according to claim 1, wherein the bulk interplanar spacing is 1.8 to 2.2 times the surface interplanar spacing.

7. The positive electrode active material according to claim 1, wherein the bulk crystal structure has a [1,0,0] projection and layered symmetry.

8. The positive electrode active material according to claim 1, wherein the surface crystal structure has [1,2,-1] projection and cubic symmetry.

9. The positive electrode active material according to claim 1, comprising at least one element selected from Group 4, Group 6, Group 13 of the periodic table and selected from Groups 8 to 10.

10. The positive electrode active material according to claim 1, comprising a bulk component represented by chemical formula 1 and a dopant component represented by chemical formula 2: Chemical Formula 1 Li a1 Ni n1 (M A y ) z O 2-b X b in, Each M A Independently selected from Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sn, Sr, Ti, V, W, and Zr. Each X is independently selected from F, P, and S. 0.9≤a1≤1.2, 0.8≤n1≤0.995, Each y is an independent real number between 0 and 0.

2. z is an integer from 1 to 5, and 0≤b≤0.1, Chemical formula 2 Li a2 Ni n2 M B y2B M C y2C O2 in, M B Transition metals selected from group 4 elements. M C Transition metals selected from group 6 elements. 0.9≤a2≤1.5, n² and y²B are each independent real numbers ranging from 0.27 to 0.39, and The sum of n² + y²B + y²C equals 2 - a².

11. The positive electrode active material according to claim 10, wherein: The bulk component is represented by chemical formula 1A and the dopant component is represented by chemical formula 2A: Chemical Formula 1A LiNi n Co y3 Al y4 O2 in, 0.9≤n≤0.995, 0.005≤y3≤0.1, and The sum of n+y3+y4 equals 1. Chemical formula 2A Li 1.2 Ni 0.33 You 0.33 M C y5 O2 in, M C is Mo or W, and 0.10≤y5≤0.16。 12. The positive electrode active material according to claim 1, wherein the reconstructed region is located on the surface of the positive electrode active material and comprises group 4 elements and group 6 elements.

13. The positive electrode active material according to claim 12, wherein the reconstructed region further comprises a group 13 element and at least one element selected from groups 8 to 10.

14. The positive electrode active material according to claim 12, wherein the thickness of the reconstructed region is 2% to 20% of the size of the primary particles of the positive electrode active material.

15. The positive electrode active material according to claim 1, comprising secondary particles, each secondary particle comprising an aggregation of primary particles. in: Each secondary particle has an average particle size D50 ranging from 10 micrometers (μm) to 18 μm, and The primary particles have an average particle size D50 ranging from 15 nanometers (nm) to 300 nm.

16. A method for manufacturing a doped, reconstructed nickel-rich positive electrode active material, comprising: Provide the main components; Provide doping components; The bulk component and the dopant component are mixed to provide an intermediate; as well as The intermediate was heat-treated in an oxidizing atmosphere. The method described therein includes a single heat treatment.

17. The method of claim 16, wherein providing the intermediate comprises mixing the bulk component and the dopant component in a weight ratio of 1:0.5 to 1:0.

001.

18. The method of claim 16, wherein: The provided body components include: A first Li compound, an Al salt, and a first solvent are mixed to form a first precursor; The first Li compound and Ni composite oxide, with an added portion, are provided to the first precursor to form a first complex, wherein the Ni composite oxide is represented by chemical formula 3; Chemical formula 3 LiNi n3 M D y6 O2 Among them, M D For Co or Fe, 0.9 ≤ n3 ≤ 0.995, and the sum of n3 + y6 equals 1; and The first composite is heat-treated, wherein... The provided doping components include: A second Li compound, a Ni oxide, a group 4 oxide, a group 6 oxide, and a second solvent are mixed to form a second precursor. Processing the second precursor; and The second precursor is heat-treated.

19. The method of claim 18, wherein the group 4 oxide is TiO2 and the group 6 oxide is MoO2 or WO3.

20. A method of operating a battery, the battery comprising: The positive electrode includes the positive electrode active material according to any one of claims 1 to 15; negative electrode; as well as The electrolyte between the positive electrode and the negative electrode.